The importance of trade for MSEs in the Indonesian F&B sector - Hasran; Krisna Gupta (Center for Indonesian Policy Studies (CIPS), 2023)
In 2019, the food & beverage (F&B) industry made the largest contribution to the nation's gross domestic product (GDP) and grew by an average of 7.78%, the highest growth among non-oil and gas industries. It is also the only non-oil and gas industry experiencing a trade surplus. In 2019, imports by this industry decreased by an average of 0.1%, while annual export growth averaged 0.7%. The F&B sector was the largest employer of Indonesian workers outside the oil and gas sector in 2019. While around a third (36%) of workers in large and medium-sized F&B companies are female, they account for more than half of workers (56% in the food industry and 58% in the beverage industry) in micro and small enterprises (MSEs).
Keywords: 330; Ernährungsindustrie; Getränkeindustrie; KMU; Globale Wertschöpfungskette; Außenhandel; Indonesien